An agent-based security framework for cooperative business networks - Cunha, Carlos R. (2013)
The actual economic paradigm is based on a strongly cooperative model that tries to support a more competitive and global organizations response. But, with cooperation comes an intrinsic need - interconnection and interoperability of information systems among business partners. This represents, in many areas, a huge organizational challenge, being the field of information, and communication security one emerging key issue and a natural enabler for cooperative behavior and to the proper establishment and support of trust among network partners. Security frameworks, that can be able to describe and act on the basis of interoperability, cooperation and proactivity, became essential to support the new needs of modern business models. This paper presented a framework that aims to contribute to a sustainable organizational information security-processes support, based on the ability to describe the allowed business process interactions among cooperative partners; furthermore, the framework presents a cooperative security perspective among partners basis on the idea that, if organizations have business cooperation, they should also have active security cooperation and regulation. If organizations, that need to cooperate, do not feel secure when they interconnect their information systems, the all cooperative perspective can fall down. Trust being one basic need for cooperation, impulse the need of a new security approach for cooperative scenarios.